Strategi pengelolaan manajemen sumber daya manusia untuk meningkatkan kinerja organisasi - Sholihin, Zainus (Maliki Interdisciplinary Journal, 2025)
Human Resource Management (HRM) is an essential part of any organization and serves as a key factor in achieving goals. HR is considered not merely a cost, but a vital asset. Effective HR management can increase organizational productivity and efficiency, especially amidst increasingly fierce global competition. This paper discusses various HR management strategies that can be implemented to improve organizational performance and explains the key concepts and positive benefits of implementing sound HRM. Furthermore, this paper aims to provide a deeper understanding of the crucial role of HRM in supporting organizational efficiency and effectiveness. Good HR management not only helps achieve short-term goals but also ensures the organization’s long-term sustainability and success. Furthermore, factors such as transformational leadership, employee development, diversity management, and results-based performance management play a strategic role in building a healthy work culture, increasing motivation and productivity.